IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM WASATHIYAH DI PONDOK PESANTREN SABILURROSYAD GASEK MALANG - Izza Safitri; Abdul Jalil; Qurroti A’yun (VICRATINA, 2022)
Lately we have all been shocked by the emergence of intolerant radical Islamic groups, where these groups are easy to heresy something, disbelieve in other groups, can even lead to hostility and conflict against groups who do not agree with the group.  The research, entitled Implementation of Wasathiyah Islamic Educational Values at the Sabilurrosyad Islamic Boarding School, discusses 3 problem formulations, namely How to Implement Wasathiyah Islamic Educational Values, How to Apply Wasathiyah Islamic Education Values, and How Wasathiyah Islamic Education Model is applied. at the Sabilurrosyad Gasek Islamic Boarding School, Malang. The method used in this research is a qualitative method using case study research. The results of the study found that there is Three Values of Wasathiyah Islamic Education include the first Ash-Siddiq (Be honest), the second Tolerance, and the third Taawun (Please Help). And as for the book, which refers to one of the books of Nashohibul Ibad, the Book of Imam Al-Ghozali, Ihya 'Ulumuddin, Ngaji Al-Hikam. As well as in its learning to apply 2 methods namely recitation and learning